1998
DOI: 10.1055/s-2007-978883
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Association Between the Insertion/Deletion Polymorphism of the Angiotensin-Converting-Enzyme Gene and Diabetic Nephropathy in IDDM Patients

Abstract: The insertion/deletion (I/D) polymorphism of the angiotensin-converting-enzyme (ACE) gene has been reported to be associated with diabetic nephropathy in IDDM. We studied the relationship between this polymorphism and diabetic nephropathy in 210 IDDM patients. Their DNA was analyzed by polymerase chain reaction to type for the presence (I) or absence (D) of the 287 bp fragment in intron 16 of the ACE gene. The relative frequency of the different genotypes was 33.8% (DD), 43.8% (ID), and 22.4% (II). There were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 23 publications
1
7
0
2
Order By: Relevance
“…Similarly MTHFR A1298C polymorphism was reported to be negatively associated with DN in the studies done among Jewish50 and Polish 48 cases. Similarly, lack of an association between kidney function and ACE (DD/II) was reported in previous studies done among Chinese,51 German,52,53 Danish,54 Turkish,4,55,56 Korean, 57 Iranian 58,59 and Dutch 60 diabetic cases.…”
supporting
confidence: 56%
“…Similarly MTHFR A1298C polymorphism was reported to be negatively associated with DN in the studies done among Jewish50 and Polish 48 cases. Similarly, lack of an association between kidney function and ACE (DD/II) was reported in previous studies done among Chinese,51 German,52,53 Danish,54 Turkish,4,55,56 Korean, 57 Iranian 58,59 and Dutch 60 diabetic cases.…”
supporting
confidence: 56%
“…The implication of ACE genotype in the pathogenesis of nephropathy in Type 1 diabetes is controversial. Many studies showed an association [6][7][8][9][10][11][12][13][14] but others were not able to provide evidence [15][16][17][18][19][20]. On the basis of meta-analyses, more data support the concept that rather the progression than the development of nephropathy is influenced by ACE genotypes [45,46], however, an effect on the development of microalbuminuria can not be entirely excluded [47].…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical studies have found that the D allele is associated with an increased risk of diabetic nephropathy [6][7][8][9][10][11][12] which have been supported by morphological findings [13,14]. However, other studies have failed to demonstrate any relationship between the ACE genotype and diabetic kidney damage [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 97%
“…In the present study, we had the advantage of a close match between the two groups of patients in a long list of potentially confounding variables. It should be noted, however, that there are several reports on type 1 diabetes without statistically significant results ( 29 , 37 ).…”
Section: Discussionmentioning
confidence: 97%